Potential chemoprotective effects of green propolis, L-lysine and celecoxib on bone marrow cells and peripheral blood lymphocytes of Wistar rats subjected to bladder chemical carcinogenesis - Dornelas,Conceição Aparecida (2014)
PURPOSE:To evaluate the genotoxicity of propolis and L-lysine, as well as their effects on the possible cellular damage in erythroblasts (bone marrow) and leukocytes (peripheral blood) caused by the carcinogen BBN (n - butyl - n {4 - hydroxybutyl} nitrosamine) in rats subjected to bladder carcinogenesis and treated with green propolis and L-lysine.METHODS: One hundred and twenty five rats were distributed into the following groups: I, IIA, IIB, III, K, L M N, X, XI, XII and XIII. Groups I to X received BBN in drinking water for 14 weeks (wks). Group I was treated with intragastric (ig) propolis at 150 mg/kg body weight, for 44 wks, beginning 30 days before start of BBN. Groups IIA and III were treated with propolis (150 mg/kg), for 40 wks, subcutaneous (sc) and ig, respectively, beginning simultaneously with BBN. On the 32nd wk, the animals of groups L, M and N were treated ig with L-lysine (300 mg/kg), celecoxib (30 mg/kg) and propolis (300 mg/kg), respectively, up to the 40th wk. The groups that received only BBN (IIB and K) were treated with water, sc and orally, respectively, for 40 wks. Groups XI, XII and XIII received respectively propolis (150 mg/kg), L-lysine (150 mg/kg) and water ig for 40 wks. After 40 wks, the surviving animals were anesthetized and subjected to femoral bone marrow aspiration and blood collection from the aorta, for CA and MNT, respectively, for investigation of genotoxicity.RESULTS: Groups IIB and K, which received only BBN and water, showed the greatest DNA damage in peripheral leukocytes (CA) and largest number of micronuclei in bone marrow erythrocytes (MNT) in relation to all other groups that received BBN and lysine and/or propolis (p<0.001).CONCLUSIONS:Both propolis and L-lysine are effective in protecting against genotoxicity, as well not being genotoxic themselves toward the cells evaluated, at the doses and times administered and according to the two tests utilized.